PENDEKATAN PEMBIMBINGAN PEMBELAJARAN KEPADA ANAK TERMARGINALKAN PADA USIA SEKOLAH DASAR (SEBUAH USULAN PEMIKIRAN) - Lydia Weniati A; Putri Ayu C. Ratulona (JURNAL PENABIBLOS, 2024)
Children aged 6-12 years are elementary school age, where children experience changes with various stages of growth and development, physical, cognitive, psychological and language. Elementary school age children experience the most strategic phase of development to explore their life potential. Marginal children of elementary school age need spiritual development and character and skill formation for their future. Parents and marginalized children, namely those living in the suburbs or on the streets, are the main targets of holistic services. Education is the main focus given, in order to realize a better phase of life for children from marginalized groups by providing learning spaces in the form of tutoring for the Word of God and school subjects that are full of skills. Teaching God's Word for children from marginalized groups to experience a life led by the holy spirit, and have a positive impact on the environment of marginalized groups. This scientific writing uses a qualitative method, a descriptive approach about the spiritual life of marginalized elementary school age children using the literature review method. Therefore, it is necessary to provide spiritual services as well as provide learning guidance to marginalized children, not only in terms of the child's character, but from a cognitive, affective and psychomotor perspective, the child will be directed and guided to become a child who believes in God and a child who has the character of Christ.